Challenges to determining whether DHA can protect against age-related cognitive decline. (February 2015) - Hennebelle, Marie; Harbeby, Emilie; Tremblay, Sébastien; Chouinard-Watkins, Raphael; Pifferi, Fabien; Plourde, Mélanie; Guesnet, Philippe; Cunnane, Stephen C
DHA, an omega-3 fatty acid, is an important constituent of brain membranes and has a key role in brain development and function. This review aims to highlight recent research on DHA's role during age-related cognitive decline and Alzheimer's disease. Animal and in vitro studies have provided some interesting mechanistic leads, especially on brain glucose metabolism, that may be involved in neuroprotection by DHA. However, results from human studies are more mitigated, perhaps due to changing DHA metabolism during aging. Recent innovative tools such as 13 C-DHA for metabolic studies and 11 C-DHA for PET provide interesting opportunities to study factors that affect DHA homeostasis during aging and to better understand whether and how to use DHA to delay or treat Alzheimer's disease.